2009
DOI: 10.1091/mbc.e08-08-0849
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of Cytoskeleton Associated Protein 4 by DHHC2 Regulates Antiproliferative Factor-mediated Signaling

Abstract: Previously, we identified cytoskeleton-associated protein 4 (CKAP4) as a major substrate of the palmitoyl acyltransferase, DHHC2, using a novel proteomic method called palmitoyl-cysteine identification, capture and analysis (PICA). CKAP4 is a reversibly palmitoylated and phosphorylated protein that links the ER to the cytoskeleton. It is also a high-affinity receptor for antiproliferative factor (APF), a small sialoglycopeptide secreted from bladder epithelial cells of patients with interstitial cystitis (IC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 57 publications
6
75
1
2
Order By: Relevance
“…Thus, it is unlikely that APF can interact with Wnt and consequently lead to the down-regulation of ␤-catenin. Instead, APF might down-modulate ␤-catenin by inhibiting the production of HB-EGF (8) and/or antagonizing the binding of tissue plasminogen activator (tPA) with CKAP4, a high-affinity receptor for APF (6,7). This speculation is based on previous findings that HB-EGF may activate the phosphatidylinositol 3-kinase/Akt pathway and in turn inhibit GSK3␤ and stabilize ␤-catenin (37), and that CKAP4 is also a receptor for tPA (38), which may activate ␤-catenin signaling by transactivating EGFR (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unlikely that APF can interact with Wnt and consequently lead to the down-regulation of ␤-catenin. Instead, APF might down-modulate ␤-catenin by inhibiting the production of HB-EGF (8) and/or antagonizing the binding of tissue plasminogen activator (tPA) with CKAP4, a high-affinity receptor for APF (6,7). This speculation is based on previous findings that HB-EGF may activate the phosphatidylinositol 3-kinase/Akt pathway and in turn inhibit GSK3␤ and stabilize ␤-catenin (37), and that CKAP4 is also a receptor for tPA (38), which may activate ␤-catenin signaling by transactivating EGFR (39).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that knockdown of DHHC2 by siRNA inhibited plasma membrane localization and the ability of APF to inhibit proliferation [14]. CKAP4 has also been predicted to undergo posttranslational modification by tyrosine sulfation, the addition of a negatively charged sulfate group to a tyrosine residue, at tyrosine 323 [25,26].…”
Section: Ckap4 Structurementioning
confidence: 99%
“…For example, CKAP4 has been shown to be required for APF-mediated signaling [11,[13][14][15][16], for gentamycin-induced cytotoxicity [17], for regulation of tPA function [10], and for SP-A-induced surfactant uptake by pneumocytes [18]. This evidence for CKAP4 mediating a wide array of cellular responses important in physiological and pathological processes, such as interstitial cystitis, druginduced cytotoxicity, pericullar proteolytic activity, and lung lipid homeostasis, provides new insights into this classically ER-resident protein.…”
Section: Introductionmentioning
confidence: 99%
“…О р и г и н а л ь н ы е и с с л е д о в а н и я Науч-практич ревматол 2012; 50(6): [33][34][35][36][37] Экспрессия генов ключевых метаболических путей, регулирующих сигнальный путь mTOR, в крови больных ОА на разных стадиях забо-левания (а -и). С -здоровые лица, LOW -подгруппа больных ОА с низкой экспрессией гена mTOR; HIGH -подгруппа больных ОА с вы-сокой экспрессией гена mTOR; ES -больные ОА на поздней стадии заболевания Обсуждение У больных ОА в подгруппе LOW метаболические на-рушения, приводящие к ингибированию гена mTOR, могут быть связаны с недостаточностью энергетического метабо-лизма, смещением баланса в сторону АМФ, что приводит к активации сигнального пути АМПК -ингибитора mTOR [18].…”
Section: результатыunclassified
“…Пальмитат в клетках регулирует 162 гена, индуцирует апоптоз и старение многих типов кле-ток [32]. Кроме того, пальмитоирование мембранных бел-ков блокирует пролиферативную активность клеток [33]. Возможно, именно это нарушение метаболизма является критическим для активного разрушения хряща, а также для развития болевого синдрома у больных ОА [16,17] на поздней стадии заболевания.…”
Section: результатыunclassified